NILAI KEADILAN DALAM MANAJEMEN KEBERSAMAAN MASYARAKAT JEPANG - Sri Sudarsih (Diponegoro University, 2018)
(Title: Value Of Justice In Japanese Community Management). The Japanese Revolution brought the glory of the country into a just and prosperous country. The success of several companies in this country has been recognized worldwide. The key to the success of these companies is because they have managed to integrate traditional and modern management. Traditional management that is rooted in a culture that is lived and carried out in daily life in the form of family principles is fully implemented. While to catch up, they are open and adopt modern management. This combination of management in turn provides the place, roles and responsibilities of each family member so that a sense of justice is achieved for all members and companies. Employee loyalty to the company can be accounted for and the stability of the company as a condition of the company's progress is fulfilled so that the company is ready to develop rapidly. The values of justice reflected in Japanese management are individuals who carry out obligations in the interest of groups as a form of commutative justice. Whereas groups that provide justice to individuals are a form of distributive justice. The balance between rights and obligations is a form of legal justice.